Case Report: Homozygous Pathogenic Variant P209L in the TTC21B Gene: A Rare Cause of End Stage Renal Disease and Biliary Cirrhosis Requiring Combined Liver-Kidney Transplantation. A Case Report and Literature Review - Gambino, Giuseppe; Catalano, Concetta; Marangoni, Martina; Geers, Caroline; Moine, Alain Le; Boon, Nathalie; Smits, Guillaume; Ghisdal, Lidia (Frontiers in Medicine, 2021)
Background: Ciliopathies are rare diseases causing renal and extrarenal manifestations. Here, we report the case of a ciliopathy induced by a homozygous pathogenic variant in the TTC21B gene. Case Description: A 47-year-old patient started hemodialysis for chronic kidney disease (CKD) of unknown origin. She presented with early onset of hypertension, pre-eclampsia, myopia and cirrhosis. Renal biopsy showed mild interstitial fibrosis, tubular atrophy, and moderate arteriosclerosis while liver pathology demonstrates grade B biliary cirrhosis. Family history revealed several cases of early-onset severe hypertension and one case of end-stage renal disease (ESRD) needing kidney transplantation at twenty years of age. Clinical exome sequencing showed homozygosis for the pathogenic variant c.626C>T (p.Pro209Leu) in the TTC21B gene. The patient underwent combined liver-renal transplantation with an excellent renal and hepatic graft outcome. Conclusions:TTC21B gene mutations can lead heterogeneous to clinical manifestations and represent an underappreciated cause of ESRD. The paradigm in diagnosis of CKD of early onset and/or of unknown origin is changing and genetic counseling should be performed in all patients and families that meet those criteria. Renal or combined liver-renal transplantation represents the best option for patients suffering from those diseases in terms of prognosis and quality of life.